STRATEGI HUMAS DALAM MEMBANGUN CITRA PERUSAHAAN (Studi Pada Indonesia Tourism Development Corporation, Bali) - Nindya Saraswati, Ni Putu Ayunda; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 2 (2018), 2018)
ABSTRACT   ITDC is building its image as a developer of world-class tourism destination, where the previous image when called BTDC which is the developer of tourism in Bali. Changes in the management company's impact on the image of the company, changes in the company's organizational structure, corporate tagline, a corporate culture that people do not know. This study uses the paradigm of post-positivism which brings together deductive logic to perform and probabilistically empirical observations using qualitative types. In the study of interactive models, Miles and Huberman is used as a data analysis technique. The results showed that the change in the management company of the BTDC became ITDC affecting corporate image so that the image of care with ITDC owned associated trust all stakeholders towards the ITDC. Strategies undertaken by publicist ITDC in building a corporate image that is doing the publications (publication), the manufacture of news (news), providing information to the public good that the public internal and external (inform or image), use paid media that is in the form of event, do social contacts (community involvement, lobbying and negotiation (lobbying and negotiation), perform social activities (social responsibility). Publicist ITDC do media monitoring to ensure a well guarded corporate image based on news stories that appeared in the media be it media, both print and online media.   Keywords: public relations strategy, ITDC Bali, corporate image